The Influence of Processing Conditions on the Sedimentation Kinetics of Highly Waxy Crude Oil; Procedia Chemistry; Vol. 15 : Chemistry and Chemical Engineering in XXI century (CCE 2015) - Loskutova Y. V.; Ryzhova N. S.; Yudina N. V.; Beshagina E. V. Evgeniya Vladimirovna (2015, 2015)
Title screen